Information-Seeking Behavior Of Students In Choosing Universitas Dehasen Bengkulu - Siska Putri; Dilmai Putra; Maryaningsih Maryaningsih (Universitas Dehasen Bengkulu, 2026)
Bengkulu as their university of choice. The problem addressed in this research is how students search for and utilize information before deciding to enroll in a particular university. The aim of this study is to understand the process, sources, and utilization of information used by students when selecting Universitas Dehasen Bengkulu. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving six new students from different study programs. The data were analyzed descriptively to identify patterns of information needs, information search, and information use. The results show that students experience uncertainty when choosing a university, which encourages them to seek information about campus facilities, tuition fees, study programs, student activities, and career prospects. Students obtain information from both informal sources such as family, friends, and alumni, and formal sources such as social media and official university promotional media. The information is compared across sources before being used as the basis for decision-making. In conclusion, information-seeking behavior helps students reduce uncertainty and strengthen their confidence in selecting Universitas Dehasen Bengkulu as their university.